Retrospective Analysis of the Clinical Efficacy of N-Acetylcysteine in the Treatment of Hepatitis B Virus Related Acute-on-Chronic Liver Failure - Wang, Meng-Lan; Yin, Xiu-Jun; Li, Xue-Lian; Wang, Fa-Da; Zhou, Jing; Tao, Ya-Chao; Wang, Yong-Hong; Wu, Dong-Bo; Chen, En-Qiang (Frontiers in Medicine, 2021)
Objective: HBV-related acute-on-chronic liver failure (HBV-ACLF) has a high mortality due to severe intrahepatic cholestasis and coagulation dysfunction, thus new treatment measures are urgently needed to improve the therapeutic effect. This study aimed to observe the efficacy of N-acetylcysteine (NAC) in the treatment of HBV-ACLF. Methods: The data of patients with HBV-ACLF admitted to West China Hospital from October 2019 to August 2020 were collected retrospectively, and they were divided into treatment group and control group according to whether they had received additional NAC treatment. The improvement of biochemistry, coagulation function and disease severity score after 14 days of hospitalization were analyzed between two groups. Results: A total of 90 HBV-ACLF patients were included, including 42 patients in treatment group and 48 patients in control group. Compared with baseline, serum TBil, DBil, TBA, GGT and ALP in two groups both decreased significantly, while PTA increased significantly. Interesting, the decrease of serum TBil, DBil and TBA and the increase of PTA in treatment group were all significantly than these in control group. Additionally, more patients in treatment group than control group changed from CTP grade C to grade B. Subgroup analysis of CTP grade C patients showed that the decrease of serum TBil, DBil and TBA and the increase of PTA in treatment group were significantly than these in control group. Conclusion: The NAC treatment may help to improve intrahepatic cholestasis and coagulation dysfunction of HBV-ACLF.